THE EFFECT OF REGIONAL REVENUE AND EXPENDITURE BUDGET REALIZATION ON ECONOMIC GROWTH IN ENREKANG REGENCY - Yasri Tarawiru; Nur Wildayanti B; Fitriani Fitriani (Journal AK-99, 2022)
The purpose of this research is to determine the effect of the revenue budget realization on economic growth in 2016-2020 period, to find out regional expenditure on economic growth in Enrekang Regency for 2016-2020 period, to find out theregional revenue and expenditure budgets realization has an effect on economic growth in 2016-2020 period. Quantitative (descriptive) analysis method, which analyzes data on the Regional Revenue and Expenditure Budgets realization on economic growth in Enrekang Regency. Quantitative method, multiple linear regression method, namely to see the effect of regional revenue (X1) and expenditure (X2) oneconomic growth (Y). The results of the study stated that from the table of results of the f-test analysis, namely the effect of regional revenue on economic growth obtained the value of t-count > t-table (-2,101 < -2,131) at a significant level of 0.05. Then there is a significant effect between revenue and the value of economic growth. So that hypothesis 1 is accepted. Based on the partial test results, on the table of t-test analysis, the effect of regional expenditure on economic growth is obtained by the value of t-count > t-table (-1.980 <-2.131) at a significant level of 0.05, so Ha is accepted, meaning that partially there is a significant effect between regional expenditure and economic growth. So that hypothesis 2 is accepted. In the study entitled the effect of regional revenue and expenditure budgets realization on economic growth in Enrekang Regency. The variable used in this study was the effect of regional revenue and expenditure budgets on economic growth being the independent and dependent variable, namely the regional revenue and expenditure budgets has a significant effect. So that hypothesis 3 is accepted.